Hungry Bunny - Wang, Margaret C.; Burnett, Alex (Atlanta, GA : Piggy Toes Press, 2007)
Hungry Bunny is very hungry. Learn colors, shapes, numbers, and more, and find out what finally satisfies his hunger in this delicious sparkling foil book!"--Back cover.
A sparkling learning book.
Keywords: Rabbits -- Juvenile fiction; Hunger -- Juvenile fiction; Numbers -- Juvenile fiction; Color -- Juvenile fiction; Counting -- Juvenile fiction; Shapes -- Juvenile fiction